Manchuria : : Papers 101-End - Great Britain Embassy (Japan); Great Britain Foreign Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1934)
Foreign Office file containing correspondence and memoranda relating to the political situation in Manchuria and Japanese military activity